News Briefs. (Computer (00189162), 2014)
Topics include the biggest distributed denial-of-service ever measured, the IPv4 address shortage, the cooling of supercomputers by immersing them in liquid, a report naming Java as the leading malware target, a new headset that beams video directly into users' eyes, an ear-based computer controlled by facial movements, software that makes cloud operations more efficient, new technology that lets Wi-Fi users borrow others' bandwidth when needed, and a sensor that helps people grow plants better.